Chicken manure as an organic fertilizer: composting technologies and impact on soil properties (a review) - M. V. Semenov; A. D. Zhelezova; N. A. Ksenofontova; E. A. Ivanova; D. A. Nikitin (Бюллетень Почвенного института им. В.В. Докучаева, 2023)
Chicken manure and composts derived from it are valuable organic fertilizers that have a positive impact on soil fertility and significantly enhance crop yields. However, the application of fresh manure can lead to excessive concentrations of nitrogen and other nutrients in the soil, as well as contamination of the soil with microorganisms that are pathogenic to humans and animals. Therefore, it is recommended to compost chicken manure prior to its use in agriculture. This review examines the composition and properties of chicken manure, the techniques involved in its composting, and its influence on the physical, chemical, and biological properties of the soil. The utilization of composted manure results in increased levels of organic carbon (on average by 1–1.5%), nitrogen (by 0.1–0.2%), and other biophilic elements. Moreover, it improves various physical properties of the soil, such as porosity, aeration, and density. Levels of pH increase (by 0.2–0.4), as well as electrical conductivity (by 2–2.5 times), and the quantity of water-resistant aggregates (by 5–10%). The application of these fertilizers also promotes biological activity, microbial diversity, microbial biomass carbon (by 25–75%), and soil enzymatic activity (phosphatase and catalase increase by 5–7 times, and urease by 3–5 times). When chicken manure is incorporated into the soil, a significant (2–4 times) increase in the population of bacteria from the phyla Firmicutes, Bacteroidetes, and Actinobacteria is observed. The necessity of investigating the effects of compost derived from chicken manure on the chemical composition and storage of soil organic matter, pore space, and the ecotrophic structure of the soil microbiome is also discussed.